Natural product of gambier (Uncaria gambier Roxb) extracts to counter against hepatotoxicity effects due to monosodium glutamate induction in male mice - Yunita Sari Pane; Yetty Machrina; Sufitni Hasan; Fitriani Lumongga; Yuki Yunanda (Wolters Kluwer Medknow Publications, 2021)
Monosodium glutamate (MSG) is often added in foods to enhance the flavor. It has adverse effect to body organs. Natural remedies, such as: gambier have been known for generations used to improve health. Substances contained in gambier, i.e.: catechins are believed to reduce the occurrence of hepatotoxicity. The study aims to analyze the effects of gambier in reducing the hepatotoxicity of MSG. This study with a posttest only control group design. Mice amount 25 (5 groups, n = 5/group). All interventions are given orally for 4 weeks. At the end of the study, it carried out euthanasia taken the liver of mice to made histopathology preparations then examine by light microscope, ×400, ×5 view field. Liver damage was found in each group with various levels of histological appearance:(I) 2 normal, 2 minimal, 1 moderate and none severe; (II) none normal, 1 minimal, 3 moderate and 1 severe; (III) 1 normal, 4 minimal, none moderate and severe;, (IV) 2 normal, 3 minimal, none moderate and severe; and (V) 4 normal, 1 minimal, none moderate, and severe. The data were analyzed using Kruskal-Wallis test. The level of liver damage among all groups was significantly different (p = 0.017). The same on the Dunn test also showed the level of liver damage in Group-II to compare with other groups (p < 0.05). The present study proves that Gambier (Uncaria gambier Roxb) can reduce occurrence of hepatotoxicity caused by MSG.